Adoption of Chemical Pesticides Under Commercial Vegetable Cultivation in Sri Ganganagar District of Rajasthan - Singh, Ajit; Jheeba, S. S.; Pramendra, Pramendra; Manjunatha, B. L.; Hajong, Dipika (Indian Journal of Extension Education, 2021)
The study was conducted in Sri Ganganagar district of Rajasthan to assess the extent of use of chemical pesticides under commercial vegetable cultivation. The primary data were collected from 100 farm households across 18 villages from 2016 to 2019. Chemical insecticides were used by all farmers whereas biopesticides and botanical pesticides were used by <5% for insect pest control in vegetables. The average number of chemical pesticide sprays in a crop cycle was 14, 15, 15 and 13 in cauliflower, cabbage, tomato and pea crops respectively. Average quantity of chemical pesticides used was 4.23, 3.87, 5.16 and 3.47 kg active ingredient per hectare in cauliflower, cabbage, tomato and pea crops respectively. The study highlights the overuse and misuse of chemical pesticides in vegetable crops where the economic part is edible unlike cotton where the economic part is non-edible. The direct negative impact of chemical pesticides on health of farm workers is estimated in the paper.